Game-Based Learning and Gamification – Case Study ``Covering all the Information the Partnership Gained from the Project`` - Paulina SPANU; Jose Alberto LENCASTRE; Marco BENTO; Gulden ILIN; Panos MILIOS (Communications of International Proceedings, 2021)
Game-based learning and Gamification are innovative pedagogical approaches used for educational purposes, but which require a strategic procedure both in terms of curriculum planning and in terms of the resources used. The aim of the article is to highlight the perceptions of adult education trainers about game-based learning and gamification at European level. The study was carried out by experts from four countries and highlighted the need to develop results available for other trainers who want to learn more about innovative pedagogical scenarios based on game and Gamification. As a result of the needs analysis, the intellectual outputs of the project were developed, which are also presented in this article.
Keywords: Cronbach's Alpha; Digital Learning; Game-Based Learning; Gamification.